Talent for the Public: Analyzing the Training Systems of Civil Servants in Latin America - del Campo García, Esther; Hernández Bonivento, José (Revista del CLAD Reforma y Democracia, 2016)
Despite of many institutional changes, Latin American States still are known by the low technical capacity of their bureaucracies. This lack of coherence between human resources and public policy needs makes talent management in the public sector an issue of outmost importance for the countries of the region. This work will focus on one aspect untreated by recent studies of public administration in Latin America: the training systems of civil servants. At first, the characteristics of national bureaucracies in the region is shown, followed by the exposition and analysis of training systems for public officials, detailing the two different models used for the generation and capture of talent in Latin American public administrations. For this purpose, 18 countries of the region are analyzed. Finally, overall conclusions of the analysis and some points of interest for capacity building and talent management in Latin American bureaucracies are presented.
Keywords: Civil Servant Training; Training Institution; Training Models; Latin America